Content and practice of realization of mechanisms of public administration in vocation and technical training development at regional level - Hren, L. M. (Ассоциация открытой дипломатии, Грузия, 2019)
The article contains an analysis conducted on the basis of normativelegal documents of vocation-and-technical training’s formation and development within the context of the education system of Ukraine. There were determined peculiarities of content and viewed the practice of using mechanisms of state management in guiding vocation-and-technical training’s development at the regional level. Perspectives of modernizing the vocation-and-technical training system for national economy development were considered.
Keywords: state management mechanisms; vocation education; vocational training; technical education